STRATEGIES FOR PROMOTING THE USE OF CONCRETE PAVEMENTS IN TANZANIA: TECHNICAL AND INSTITUTIONAL CONSIDERATIONS - Mfinanga, D. A.; Bwire, H. (Tanzania Journal of Engineering and Technology, 2018)
High-type roads in Tanzania have been predominantly of asphaltic concrete construction. This ever enlarging and ageing asphaltic road network represents increasing resource requirements on the road agency in the form of maintenance. Limited resources coupled with the ever sky-rocketing costs of petroleum products and the competing demands of social economic developments, presupposes the need to look for alternative road construction technology that is more cost-effective and resource optimising. Experience gained from developed and some developing countries where concrete pavements have been widely used suggests the potential of this type of pavement in many developing countries. This paper discusses the technical aspects of design and construction- and maintenance-related aspects of concrete pavements. The discussion extends further to highlight issues pertaining to the performance of concrete pavements and strategies for promoting the use of concrete pavements in Tanzania. Conclusions and recommendations are made with suggestions on how to start implementing the proposed strategies.